(untitled) (Biological Sciences - PJSIR, 2001)
Hemicyanine dyes are effective voltage sensitive probes in biomembranes (Loew et a11979; EphardtandFromherz 1989). The probing of rapid changes of electrical potential in biological membrane has been studied in the light of spectroscopic behaviour of these dyes (Ephardt and Fromherz 1993). The physical behaviour of surfactant micelle can be viewed upon as a pseudo model for biomembranes to study the interactions of biological systems with various additives, for instance anesthesiatics.